A Fast-Reduced Model for an Innovative Latent Thermal Energy Storage for Direct Integration in Heat Pumps - Valeria Palomba; Andrea Frazzica (Applied Sciences, 2021)
In the present paper, the numerical modeling of an innovative latent thermal energy storage unit, suitable for direct integration into the condenser or evaporator of a heat pump is presented. The Modelica language, in the Dymola environment, and TIL libraries were used for the development of a modular model, which is easily re-usable and adaptable to different configurations. Validation of the model was carried out using experimental data under different operating modes and it was subsequently used for the optimization of a design for charging and discharge. In particular, since the storage unit is made up of parallel channels for the heat transfer fluid, refrigerant, and phase change material, their number and distribution were changed to evaluate the effect on heat transfer performance.